Social representations of men on family planning - Mônica dos Santos Bezerra; Dafne Paiva Rodrigues (Rev Rene)
Family Planning consists of a net of actions performed by a multiprofessional team that seeks to provide sexual and reproductive health. To apprehend men’s social representations on Family Planning (FP), focusing on nurses’ participation was the objective of this study, based on the Theory of Social Representations, carried out at a public hospital in Fortaleza-CE-Brazil, with 13 men that participated in the educational activity of FP, from June to September 2009. The concept of FP for them was defined as a place for discussions on the decision of having or not having children and important concerning the financial aspect. The educational activity accomplished by the social worker was considered important. It was concluded that man still don’t see themselves as active participants in the service and that the discussions go beyond children, valuing citizenship notions as well as care with their own health.